2016
DOI: 10.15218/zjms.2016.0034
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic urticaria with Helicobacter Pylori infection in Erbil: A case-control study

Abstract: 4Recent observations had suggested a possible Background and objective: Chronic urticaria is one of the most frequent skin diseases and still its etiology is recognized only in a minority of cases. Some recent studies point out to infections due to Helicobacter Pylori as being of major importance in the pathogenesis of chronic urticaria. This study aimed to find out the association of chronic urticaria with H. pylori. Methods: A case-control study was conducted in Erbil city within the period of April 1 st , 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
6
12
0
Order By: Relevance
“…This study found that patients with O blood group were more susceptible to H. pylori infection and AB blood group was less prone to infection. This results was consistent with other studies that condacted in Ethiopia and Nigeria [43], [24], and contrary to some previous studies that performed in Egypt and Erbil-Iraq explaining that the O blood group did not act as a risk factor for H. pylori infection [41], [36]. The higher susceptibility of O blood group individuals to H. pylori infection is most probably due to the higher frequency of secretor status in O blood group individuals or may be due to the H antigen represents an important receptor expressed in Vol.18.Issue 1,April 2020…”
Section: Discussionsupporting
confidence: 92%
“…This study found that patients with O blood group were more susceptible to H. pylori infection and AB blood group was less prone to infection. This results was consistent with other studies that condacted in Ethiopia and Nigeria [43], [24], and contrary to some previous studies that performed in Egypt and Erbil-Iraq explaining that the O blood group did not act as a risk factor for H. pylori infection [41], [36]. The higher susceptibility of O blood group individuals to H. pylori infection is most probably due to the higher frequency of secretor status in O blood group individuals or may be due to the H antigen represents an important receptor expressed in Vol.18.Issue 1,April 2020…”
Section: Discussionsupporting
confidence: 92%
“…The greatest prevalence (34.44%) of H. pylori infection showed among patients aged 21-30 years, whereas the lowest rate (20.83%) was happened in patients <20 years. This result agreed to other studies conducted in Saudi Arabia, Egypt, Diyala-Iraq, Erbil-Iraq, and Nigeria (Karima et al, 2006;Hwaid et al, 2013;Haggag et al, 2016;Muhemmed and Mohammed, 2016;Samson et al, 2018), and it is differed from other prior studies that revealed great prevalence rate of H. pylori infection generally recorded in more than 40 years (Hussen et al, 2013;Tawfeeq et al, 2013;Jaka et al, 2016). The differences between the present results and results of the other studies may be due to the nutrition status of the patients, socioeconomic status, inadequate sanitation, water supply, and environment condition (Al-Mossawei et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that patients with O blood group were higher prone to infection and AB blood group lower to infection. This result was corresponding to other studies that manifesting the greater sensitivity of O blood group to H. pylori infection (Tdege et al, 2005;Abdulridha, 2013;Reiisi et al, 2017;Christian et al, 2018) and opposed with some former studies which explained that the O blood group did not act as a risk factor for H. pylori infection (Zhubi et al, 2011;Shaldoum, 2015;Muhemmed and Mohammed, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…Acute urticaria occurs days to weeks, producing wheals that rarely may last more than 12 hours, and complete resolution of the lesions may occur within six weeks of onset. In comparison, daily episodes lasting more than six weeks are designated as CU [ 3 ]. Both children and adults can develop urticaria, although it is more common in adults, and females are more affected than males [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is thought that infection with H . pylori increases the permeability of the stomach lining and thus increases the exposure to allergens in the gastrointestinal tract [ 3 ]. Also, the immune response to H .…”
Section: Introductionmentioning
confidence: 99%